Look and Find, Peter Rabbit : The Tailor of Gloucester, Two Bad Mice, Mrs. Tiggy-Winkle, Ginger and Pickles and More! - Tiritilli, Jerry (Lincolnwood, Ill. : Publications International, 1992)
Readers are asked to search for characters and items from famous legends.
Keywords: Picture puzzles -- Juvenile literature; Legends; Pictorial works; Juvenile literature; Fiction; Illustrated works